Public policies in Portuguese education: The path to inclusion for all - Alves, I.; Fernandes, D. (International encyclopedia of education, 2023)
Educational policy and legislation in Portugal have been, since the 70s, on a path to developing a more inclusive education system for all. With a focus on the Portuguese context, this chapter presents an overview of the development of educational public policies toward inclusion. The development of inclusive education systems requires a joined-up approach that includes not only a focus on “special” groups, but on developing inclusive curricula and pedagogies (including assessment), designed with learner diversity as a starting point aiming at realizing the rights of all learners to education in terms of access to, participation, and success in education.